Cкладні луки у похованнях ранньосередньовічного катакомбного могильника біля с. Верхній Салтів - Аксьонов, В.С. (Археологія, 2016)
Публікуються рештки складних луків, котрі було виявлено в катакомбі 127 Верхньо-Салтівського IV могильника та 65 Верхньо-Салтівського I некрополя. In 2015, at the fourth area of a Saltiv-Mayaky culture catacomb burial ground near the village of Verkhniy Saltiv (ВСМIV) in Vovchansk Region of Kharkiv Oblast, in catacomb 127, two side end plates from a bow were found. Metal plated binding plates, an iron crampon, and a frame type hook, all from a quiver, as well as four triangular barbed arrowheads were found with them. Side end covers for a bow found in chamber evidence that a part of a deliberately broken compound bow was put there. The bow represented the first line of development of «the Early Khazar» bows, according to Ye.V. Kruhlov. Fragments of four bone plates from a same type bow were found in the funeral chamber of catacomb 65 in ВСМ-I (excavated by V.H. Borodulin in 1990). Plates for bow were found in catacomb 65 together with iron plated quiver covers, two quiver loops, a quiver hook of plated type, seven barbed arrowheads, and a bronze loop from a bow case. In the chamber, two fragmented end side covers, a fragment of a shoulder cover, and a fragmented side middle cover for a bow were found. The elements of belt suite in the catacombs allow dating these burial assemblages by the middle and the second half of the 9th century. The remains of compound bows found in the catacombs evidence that the Alans at Verkhniy Saltiv used compound bows with side end covers, while found at other Alans’ sites of SaltivMayaky culture of the Siverskyi Donets River basin (Dmytrivka, Mayaky, Staryi-Saltiv burial grounds, graves from Mayaky settlement territory) are the remains of bows with frontal end plates-shuttles represented the very «Saltiv» type of compound bows (the second line of development of the «Early Khazar» bows). The fact of the presence of various types of compound bow in the Alans’ assemblages of the region needs to be explained. В 2015 г. на четвертом участке катакомбного могильника салтово-маяцкой культуры у с. Верхний Салтов (ВСМIV) (Волчанский р-н Харьковской обл.) в катакомбе 127 были обнаружены две концевые боковые накладки на лук. Рядом с ними находились металлические пластинчатые оковки от колчана, железная колчанная скоба, колчанный крючок рамчатого типа и четыре трехлопастных черешковых наконечника стрелы. Найденные в камере концевые боковые накладки на лук указывают, что в камеру была помещена часть преднамеренно сломанного сложного лука представляющего первую линию развития «раннехазарских» луков, по Е.В. Круглову. Фрагменты четырех костяных накладок на лук этого же типа были обнаружены в погребальной камере катакомбы 65 ВСМ-I (раскопки В.Г. Бородулина в 1990 г.). В катакомбе 65 накладки на лук сопровождались железными пластинчатыми оковками колчана, двумя колчанными петлями, колчанным крючком пластинчатого типа, семью черешковыми наконечниками стрел, бронзовой петлей от налучья. В камере были найдены две фрагментированные боковые концевые накладки, фрагмент плечевой накладки и фрагментированная боковая серединная накладка на лук. Найденные в катакомбах элементы поясной гарнитуры позволяют датировать данные погребальные комплексы серединой — второй половиной IX вв. Найденные в катакомбах остатки сложных луков свидетельствуют, что аланы Верхнего Салтова использовали сложный лук с боковыми концевыми накладками, тогда как на других аланских памятниках салтово-маяцкой культуры бассейна Северского Донца (Дмитриевский, Маяцкий, СтароСалтовский могильники, погребения с территории Маяцкого селища) найдены остатки луков с фронтальными концевыми накладками-челночками, представляющими собственно «салтовский» тип сложных луков (вторая линия развития «раннехазарских» луков). Факт присутствие в аланских комплексах региона разных типов сложного лука требует своего объяснения.